American Government : Readings and Cases - WOLL, Peter (Pearson Prentice Hall, 2004)
Representing both classic and contemporary documents and writings, the selections include essential political documents, major Supreme Court cases, and a wide variety of commentary and analysis by theorists, journalists, and leading political figures. The up-to-date, relevant material stimulates the reader's interest and gives fresh perspectives on how our government works.